Perceptions of organizational justice in incentive contracts and their effect on congruence between personal and organizational goals - Klein, Luciana; Colauto, Romualdo Douglas (Review of Business Management, 2020)
Purpose – This research aims to verify if perceptions of organizational justice in incentive contracts have a positive effect on the congruence between personal and organizational objectives in companies with decentralized structures. Design/methodology/approach – The research is quantitative. We used a questionnaire as the form of data collection. The instrument consists of 39 statements to test the theoretical hypotheses through structural equation modeling. The accessibility sample consisted of 140 managers of Brazilian companies. Findings – The results indicate that: (a) multiple performance measures increase the perception of distributive and procedural justice; (b) quality feedback leads to the understanding that incentive contracts are fair; (c) disregarding uncontrollable aspects by managers in performance evaluations does not lead to the perception of procedural and distributive justice; (d) perceptions of organizational justice have a positive effect on the congruence between personal and organizational goals. Originality/value –In addition to contributing to the advancement of knowledge in the managerial area, the findings of this research may support policies for the formulation of incentive contracts in Brazilian companies with decentralized structures, and this aspect represents a business and practical contribution for company managers and owners.